Problems Faced by the Agricultural Sector and Solutions for the Impending Food Crisis in Sri Lanka - Udara I.W.A.S.; Somabandu B.P.S.; Jayakody J.A.B.U.; Amerasinghe N.D.K.; D.I. De Silva; Rivoni De Zoysa (International Journal of Engineering and Management Research, 2022)
The purpose of this research was to pinpoint the challenges faced by Sri Lankan farmers as a result of the financial crisis, as the country's government failed to boost domestic production of organic pesticides and fertilizers or offer farmers subsidies to purchase them. Crop yields were destroyed by the unexpected policy change. Average yields of rice, a staple food in Sri Lanka that was previously produced successfully and even exported, were reduced by about 30%. The Department of Census and Statistics Agriculture and Environment Statistics Division gathers, analyzes, and disseminates data pertaining to this crisis. The Division compiles statistics on the extent and production of paddy as well as other temporary and seasonal crops, livestock, and production costs. The main goal of this study is to provide solutions to the problems that Sri Lankan farmers face, such as those related to production, marketing, and finances. The “AgroPro” website, which we have implemented, is one of the best solution providers in Sri Lanka for the aforementioned crisis. The purpose of this website is to provide solutions and sample techniques, after investigating the goal, primary data was gathered from the farmers. Findings: To learn about the farmers' experiences with production, marketing, and financial issues. This study aids in boosting agricultural productivity and encourages farmers to produce more goods. originality and value. Extreme care was taken to provide pertinent explanations in vernacular to enable the respondents to respond as precisely and confidently as possible.